Lock, stock, and barrel: A comprehensive assessment of the determinants of terror - Martin Gassebner; Simon Luechinger (Center for Economic Studies and ifo Institute (CESifo), 2011)
We assess the robustness of previous findings on the determinants of terrorism. Using extreme bound analysis, the three most comprehensive terrorism datasets, and focusing on the three most commonly analyzed aspects of terrorist activity, i.e., location, victim, and perpetrator, we re-assess the effect of 65 proposed correlates. Evaluating around 13.4 million regressions, we find 18 variables to be robustly associated with the number of incidents occurring in a given country-year, 15 variables with attacks against citizens from a particular country in a given year, and six variables with attacks perpetrated by citizens of a particular country in a given year.
Keywords: D74; F51; F52; H56; K42; 330; causes of terrorism; poverty and terrorism; panel estimations; extreme bounds analysis; Politische Gewalt; Panel; Extremwerttheorie; Schätzung; Welt